Generation of financial inclusion through the strengthening of small and micro entrepreneurs in marginal rural and urban areas in Peru - Marengo Murga, Víctor Enrique (2022)
Through a loan fund financed by the National Bank and the Peruvian government's Cooperation Fund for Social Development (FONCODES), the Small and Microenterprise Promotion Programme (PAME) provides loans to small and microenterprises in rural and peri-urban areas excluded from the formal financial system to develop productive, commercial and service activities, using financial institutions with experience in microfinance, giving priority to women entrepreneurs. (Foncodes, 2013) As of 31 December 2018, PAME's financial assets amounted to 454,867 loans for a total value of 1,429 million soles. The geographical coverage is 23 departments, 122 provinces and 771 districts. At the end of December 2018, 51.0% of loans were for women entrepreneurs, 55.7% for the two highest poverty quintiles, 72.7% for working capital and 77.3% for rural areas. (Midis et al., 2018) With these achievements, the FONCODES - Banco de la nación trust fund has contributed to the creation, development and strengthening of formal credit markets for financial services to vulnerable and previously disadvantaged groups in society, based on mutual trust between consumers and financial institutions. (Foncodes, 2013).